Two vision-guided vehicles : temporal coordination using nonlinear dynamical systems - Santos, Cristina (2007)
This article addresses the problem of generating timed trajectories and temporally coordinated movements for two wheeled vehicles, when relatively low-level, noisy sensorial information is used to steer action. The generated trajectories have controlled and stable timing (limit cycle type solutions). Incoupling of sensory information enables sensor driven termination of movement. We build on a previously proposed solution in which timed trajectories and sequences of movements were generated as attractor solutions of dynamic systems. We present a novel system composed of two coupled dynamical architectures that temporally coordinate the solutions of these dynamical systems. The coupled dynamics enable synchronization of the different components providing an independence relatively to the specification of their individual parameters. We apply this architecture to generate temporally coordinated trajectories for two vision-guided mobile robots in a non-structured simulated environment, whose goal is to reach a target within a certain time independently of the environment configuration or the distance to the target. The results illustrate the robustness of the proposed decision-making mechanism and show that the two vehicles are temporal coordinated: if a robot movement is affected by the environment configuration such that it will take longer to reach the target, the control level coordinates the two robots such that they terminate approximately simultaneously